Remarks on “the Only Original Right Belonging to Every Man by Virtue of His Humanity” - FAGGION, Andrea (Faculdade de Filosofia e Ciências, 2015)
Kant compares a merely empirical doctrine of right to the wooden head in Phaedru’s fable, i. e. a head that has nobrain (MS AA 06: 229). An a priori right may be acquired or innate. According to Kant, there is only one innate right (MS AA 06: 237). That only one innate right is freedom. In that context, freedom means “independence from being constrained by another’s choice” (MS AA 06: 237). As a moral right, such a right implies reciprocity. This being so, it is a right to be held “insofar as it can coexist with the freedom of every other in accordance with a universal law” (MS AA 06: 237). The reason why it is an innate right is that it is a “right belonging to every man by virtue of his humanity” (MS AA 06: 237). This paper aims to clarify a few issues regarding our innate right to freedom. To start with, we need a deeper understanding of the meaning of freedom as independence from being constrained by another’s choice. I will claim that such an independence should be understood as absence from fraudand violence. Following, it is in order to analyze the condition according to which freedom is a right: coexistence with the freedom of every other in accord with a universal law. I will claim that such a condition does not imply political authority. Finally, we have to handle the connection between the innate right to freedom and our humanity. I will claim that the innate right to freedomcannot be disconnected from the second formula of the categorical imperative.